2016
DOI: 10.1099/jgv.0.000426
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of de novo translation of host cells by manipulation of PERK/PKR and GADD34-PP1 activity during Newcastle disease virus infection

Abstract: Viral infections result in cellular stress responses, which can trigger protein translation shutoff via phosphorylation of eukaryotic initiation factor 2 alpha (eIF2a). Newcastle disease virus (NDV) causes severe disease in poultry and selectively kills human tumour cells. In this report, we determined that infection of HeLa human cervical cancer cells and DF-1 chicken fibroblast cells with NDV maintained protein at early infection times, 0-12 h post-infection (p.i.), and gradually inhibited global protein tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 37 publications
1
33
0
Order By: Relevance
“…In order to address this question, we determined the activation of PERK/eIF2 α signaling cascade at different time point postinfection. Coincided with our previous report (Liao et al, 2016), NDV infection activated the PERK/ eIF2α signaling cascade by exhibiting increased phosphorylation of PERK and eIF-2α, as well as the increased level of CHOP expression. (Fig.…”
Section: Chop Is Involved Via Pkr Activation In the Decrease In Cyclisupporting
confidence: 84%
See 3 more Smart Citations
“…In order to address this question, we determined the activation of PERK/eIF2 α signaling cascade at different time point postinfection. Coincided with our previous report (Liao et al, 2016), NDV infection activated the PERK/ eIF2α signaling cascade by exhibiting increased phosphorylation of PERK and eIF-2α, as well as the increased level of CHOP expression. (Fig.…”
Section: Chop Is Involved Via Pkr Activation In the Decrease In Cyclisupporting
confidence: 84%
“…A previous report (Liao et al, 2016) from our lab showed that NDV infection activates the PERK/ eIF2α cascade and inhibits protein translation of the host cells, while viral protein NP levels increase. C/ EBP homologous protein (CHOP) is a downstream effector of PKR/ eIF2α/ATF4 and is also known as "growth arrest and DNA damageinducible gene 153" (GADD153).…”
Section: Chop Is Involved Via Pkr Activation In the Decrease In Cyclimentioning
confidence: 75%
See 2 more Smart Citations
“…PKR is another ISG to be activated after viral infection and is been related to the reduction in protein synthesis 46 . In chicken cells challenged by NDV, PKR undergoes autophosphorylation and phosphorylates the eIF2α subunit 10 . Phosphorylation of eIF2α turns it into an inhibitor of the guanine nucleotide exchange factor eIF2B and prevents the formation of the translation initiation complex eIF2:GTP:tRNA Met that is required for the initiation of protein synthesis 15 .…”
Section: Discussionmentioning
confidence: 99%